Bacillus Penicillin Acelase, A Key Catalyst in the Modern Antibiotic Era: A Literature Review - Purnamasari, Lora (RADINKA JAYA UTAMA PUBLISHER, 2025)
Penicillin acylase from the genus Bacillus plays an irreplaceable role as a key catalyst in the modern antibiotic era. This enzyme essentially facilitates the production of 6-aminopenicillanic acid (6-APA), a vital precursor for various semisynthetic beta-lactam antibiotics that continue to be the mainstay in the fight against bacterial infections. The aim of this study was to review Bacillus Penicillin Acylase: A Key Catalyst in the Modern Antibiotic Era,